2006
DOI: 10.1577/a05-079.1
|View full text |Cite
|
Sign up to set email alerts
|

Developing Methods for Harvesting Rosy Red Fathead Minnow Eggs

Abstract: We evaluated the effectiveness of different types of spawning substrates in retaining the eggs of rosy red fathead minnow Pimephales promelas, the potential substrate preference of the fish, and the effectiveness of different concentrations of sodium sulfite for detaching eggs from substrates without affecting egg survival. Egg adherence was determined by placing replicate sections of four types of conveyor belt material of varying roughness into a pool stocked with fathead minnow. A screened tray was suspende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…After treatments, egg samples from each of the four mat sections The remaining eggs from all four treatments were placed in a hatching system similar to that used by Masson et al (2006), which consisted of 50-mL hatching tubes with a flow of aerated water drawn from a deep well and delivered through sealed pipes. One half was disinfected in a 150-mg/L formalin bath for 30 min (a common industry practice).…”
Section: Methodsmentioning
confidence: 99%
“…After treatments, egg samples from each of the four mat sections The remaining eggs from all four treatments were placed in a hatching system similar to that used by Masson et al (2006), which consisted of 50-mL hatching tubes with a flow of aerated water drawn from a deep well and delivered through sealed pipes. One half was disinfected in a 150-mg/L formalin bath for 30 min (a common industry practice).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, parasites may be transferred from adults to the young, and any wild fish accidentally stocked with the broodfish may spawn and be mixed together with the fathead minnow crop. A new hatchery method for fathead minnow (Clemment and Stone 2004;Masson et al 2006;Horne et al 2010) involves supplying spawning substrate on which males will establish nests to collect eggs for indoor hatching. Stocking fry from a hatchery provides control over density, separates adults from young, and excludes unwanted fish species.…”
mentioning
confidence: 99%
“…However, the hatching data were more variable than in other studies. Kahl et al (2001) reported a hatching percentage of 84 6 6.7% for fathead minnow eggs, and Masson et al (2006) obtained a hatching percentage of 49-54%. Diet was not an experimental variable either in Kahl et al (2001) or Masson et al (2006).…”
Section: Discussionmentioning
confidence: 99%
“…Kahl et al (2001) reported a hatching percentage of 84 6 6.7% for fathead minnow eggs, and Masson et al (2006) obtained a hatching percentage of 49-54%. Diet was not an experimental variable either in Kahl et al (2001) or Masson et al (2006). No difference in hatching percentage of the eggs or larval weights were observed in Nile tilapia Oreochromis niloticus fed diets containing either soybean oil or fish oil (El-Sayed et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation